RELEVANCE OF SOCIAL CAPITAL IN KAMPUNG ARRANGEMENT IN KAMPUNG PISANG, MAKASSAR, INDONESIA - Risma Ranreng; Hanny Wahidin Wiranegara; Yayat Supriatna (Universitas Trisakti, 2017)
Improving poor conditions of the kampung in urban areas can be solved without evictions. Eviction is not a good strategy as it will eliminate the uniqueness of kampung characteristics. Aims: This study was aimed to find out the relevance of social capital in kampung arrangement and also to understand the most influential element of the social capital and its role on the arrangement of kampung in Kampung Pisang. Methodology and results: The study investigated the elements of social capital that affect the activities in every phase in kampung arrangement process. This was done through the analysis of data resulted from the questionnaire and interview surveys on the residents of Kampung Pisang. The result showed the most influential element of social capital is the social network in participation variable. Conclusion, significance and impact study: Participation as an element of social capital plays a major role in kampung arrangement in Kampung Pisang, Makassar city in Indonesia. By participation, the relevance of social capital in kampung arrangement is developing people’s knowledge about the environmental quality and using it in the improvement of physical environmental condition. This paper showed that kampung arrangement could be done by using social capital to hinder evictions.